2016
DOI: 10.5966/sctm.2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Human Cardiomyocytes Prior to Birth by Integration-Free Reprogramming of Amniotic Fluid Cells

Abstract: The establishment of an abundant source of autologous cardiac progenitor cells would represent a major advance toward eventual clinical translation of regenerative medicine strategies in children with prenatally diagnosed congenital heart disease. In support of this concept, we sought to examine whether functional, transgene-free human cardiomyocytes (CMs) with potential for patient-specific and autologous applications could be reliably generated following routine amniocentesis. Under institutional review boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Recently, Jiang et al . 45 showed that hAFs can be reprogrammed and subsequently used to generate functional CMs with robust and highly organized myofilament structures. In this study, we demonstrated that if the hAFs present the cardiopoietic phenotype (high expression of OCT4, SSEA4, CD90), it is possible to obtain CM-like cells that recapitulate the iPS- or ES-cell-derived CM phenotype with a time- and cost-saving method that avoids cell reprogramming and all the risks related to iPS cell utilization 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jiang et al . 45 showed that hAFs can be reprogrammed and subsequently used to generate functional CMs with robust and highly organized myofilament structures. In this study, we demonstrated that if the hAFs present the cardiopoietic phenotype (high expression of OCT4, SSEA4, CD90), it is possible to obtain CM-like cells that recapitulate the iPS- or ES-cell-derived CM phenotype with a time- and cost-saving method that avoids cell reprogramming and all the risks related to iPS cell utilization 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the quest is now on defining the most suitable cell to efficiently induce iPS from and since amniotic fluid stem cells are immature fetal progenitors endowed with some degree of instrinsic pluripotency and active expression of embryonic genes including OCT4, NANOG, and SOX2 (Loukogeorgakis and De Coppi, 2017 ), they represent an ideal candidate. Recent studies have reported that murine and human AFSC can be reprogrammed into iPS more easily than adult stem cells by applying either transgene-free approaches, like chemical defined conditions via stimulation with the histone deacetylase inhibitor valproic acid (Moschidou et al, 1953 ), as well as non-integrating methods by episomal plasmid, transposon system, sendai virus or mRNA delivery by lipofection (Jiang et al, 2016 ; Slamecka et al, 2016 ; Bertin et al, 2017 ; Velasquez-Mao et al, 2017 ); notably the obtained AFSC-iPS have been proven capable of functional cardiac differentiation, thus providing important impact for future cardiac regenerative therapy and specific relevance for the treatment of neonatal cardiac congenital disease (Jiang et al, 2016 ; Velasquez-Mao et al, 2017 ). Indeed, hAFSC can be effortlessly harvested during prenatal diagnosis, treated by gene therapy and iPS technology to derived healthy myocardial and cardiovascular cells to be then processed by tissue engineering approaches so to provide cardiac grafts developed in parallel with gestation and promptly implanted in utero or at birth.…”
Section: Fetal Progenitors: Amniotic Fluid Stem Cells For Cardiac Repmentioning
confidence: 99%
“…Finally, hiPSC-derived CMs differentiated using both dECMs showed percentages of spontaneous beating foci comparable to the same cells differentiated using Matrigel ® , while the percentage of the contracting area in Cardiopoietic AF-derived CMs was surprisingly significantly higher in both the Cor TM PATCH and Matrix Patch TM than in the control cells. Even if this percentage never exceeded 30% of the total area, it was still a promising result, since very few groups were able to obtain beating CMs from amniotic stem cells without prior reprogramming [ 2 , 44 , 45 ]. This was possibly because, as expected [ 5 , 46 , 47 ] CMs with different levels of maturity were obtained, and a scaffold with a rigid elasticity niche may strongly promote beating induction, in line with what was reported by Hirata and colleagues [ 48 ].…”
Section: Discussionmentioning
confidence: 99%